-3y-2=-2y

Simple and best practice solution for -3y-2=-2y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3y-2=-2y equation:


Simplifying
-3y + -2 = -2y

Reorder the terms:
-2 + -3y = -2y

Solving
-2 + -3y = -2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '2y' to each side of the equation.
-2 + -3y + 2y = -2y + 2y

Combine like terms: -3y + 2y = -1y
-2 + -1y = -2y + 2y

Combine like terms: -2y + 2y = 0
-2 + -1y = 0

Add '2' to each side of the equation.
-2 + 2 + -1y = 0 + 2

Combine like terms: -2 + 2 = 0
0 + -1y = 0 + 2
-1y = 0 + 2

Combine like terms: 0 + 2 = 2
-1y = 2

Divide each side by '-1'.
y = -2

Simplifying
y = -2

See similar equations:

| -7x^3*8x^2= | | 9x^2+24x=9 | | 5m^2=112+8m | | p^2+3p^3-3p-1=0 | | 11-x+3=3n+3n | | G(t)=t+5 | | 2(v-5)+7v=4 | | 2x+8=360 | | -8n= | | 10x-6x=25-25 | | 62=9g | | 53=9g | | 44=9g | | 35=9g | | 26=9g | | 17=9g | | 4x+10(x+2)=60 | | X^2-5=3x+5 | | 8=9g | | 5y=-3x+14.50 | | 5r-1=19whatisr | | 10-7y=10 | | (x+2y)(x+5y)= | | 4(2x-3)=x+7 | | 8x-12=x+7 | | 4t^2+-9t=9 | | X^2-5x+6=2x-4 | | x^2-63+2x=0 | | 600x=800x(x-.75) | | 5(12-3x)-9x=4(3-2x) | | -1.5x-5=-11 | | 7(x)=56 |

Equations solver categories